Metabolites study on 5‐O‐methylvisammioside in vivo and in vitro by ultra high performance liquid chromatography coupled to quadrupole time‐of‐flight mass spectrometry. Issue 12 (29th April 2019) - Fan, Xueyan; Liu, Xiaochen; Meng, Caifeng; Liu, Ruina; Zhang, Zijian; Wang, Chunying
Abstract: 5‐O‐Methylvisammioside is one of major chromones of Radix Saposhnikoviae possessing definite pharmacological activities, but there are few reports with respect to the metabolism of 5‐O‐methylvisammioside. In this work, metabolites in vivo were explored in male Sprague‐Dawley rats and in vitro investigated on rat intestinal bacteria incubation model and were identified by using ultra high performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry. An online data acquisition method based on a multiple mass defect filter and dynamic background subtraction was developed to trace all probable metabolites. As a result, 26 metabolites in vivo (including 18, 15, 10, and 10 in rat urine, faece, bile, and blood) and 7 metabolites in vitro were characterized, respectively. Additionally, the main metabolic pathways in vivo and in vitro, including deglycosylation, deglycosylation + demethylation, deglycosylation + oxidation, N‐acetylation, and sulfate conjugation, were summarized by calculating the relative content of each metabolite. The obtained results significantly enriched our knowledge about 5‐O‐methylvisammioside metabolism and will lead to a better understanding of its safety and efficacy.